The association between demographic and attitude factors with the practice of malaria prevention among the rural community in Purworejo district, Indonesia - Farindira Vesti Rahmasari; Winny Setyonugroho; I Ketut Swarjana; Desto Arisandi; Tri Wulandari Kesetyaningsih (Universitas Muhammadiyah Surabaya, 2021)
Abstract Malaria is one of the global health problems that is faced by many countries, including Indonesia. This study aimed to examine the association between demographic and attitude factors with malaria prevention in the rural areas of Purworejo District, Indonesia. A community survey was conducted in Purworejo District that involved 147 respondents by using simple random sampling to select the respondents. A questionnaire interview was used to collect data about demographic factors, attitudes, and malaria prevention practices. A Chi-square test was performed to examine the association between demographic and attitude factors with the practice of malaria prevention in the community. Among 147 respondents, 80 (54.4%) respondents conducted malaria prevention practice using bed mosquito net in their own houses. Demographic factors such as education level (p<0.001), occupation (p=0.016), and attitude factor (p=0.006) were significantly associated with the use of bed mosquito net for malaria prevention practice. Meanwhile, 63 (42.9%) respondents used ventilation mosquito net for malaria prevention practice. Demographic factors such as education level (p<0.001), age groups (p=0.005), occupation (p=0.002), and attitude factor (p=0.001) were associated significantly with the use of ventilation mosquito net for malaria prevention practice. Overall, malaria prevention by using both bed and ventilation mosquito nets were very low percentages. Keywords : Malaria, prevention practice, mosquito net, IndonesiaCorrespondence : farindira.vesti@gmail.com